(untitled) (Huellas, 2020)
The aim of this paper is to describe labor sex division in the field of farm production within the rural area in the east of the province of Mendoza, mainly focusing on women’s labor. To accomplish this task, we designed a case study methodology strategy. The place for the study constitutes a non-irrigated area in the north–east region, which is composed of domestic groups historically devoted to extensive cattle raising. This article has been organized as follows: First, we state some general theoretical considerations related to gender, work and farming systems, together with some historical background. Then, we move to the local scale, and make a synthesis of the characteristics of labor sex division within the area under study, making an emphasis on the livestock production. Finally, we show the active key role women play in the cattle raising industry.